Development of An Interactive E-Module Based on Blended Learning to Enhance Student Independence and Learning Outcomes - Novia Andriani; Kusumawati Dwiningsih (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the feasibility and effectiveness of interactive e-modules based on blended learning to increase independence and learning outcomes on acid-base materials. This research is development research using the Borg & Gall model which consists of ; 1) Research and Information collection, 2) Product planning, 3) Product development, 4) Product validation, 5) Product revision, 6) Product trial. The subjects of this study were chemistry lecturers and chemistry teachers as well as students of SMA Negeri 1 Krembung Sidoarjo who took chemistry specialization. The instruments used were review and validation sheets, learning independence questionnaires, response questionnaires, and learning outcomes test sheets. Data analysis using the N-gain to determine the increase in student independence and learning outcomes. The validation results are processed using the mode of each statement, the results of content validity get mode 5 with very valid criteria, and construct validity get mode 4 with valid criteria. The results of this study indicate that learning chemistry using interactive e-modules based on blended learning can increase learning independence with an n-gain value at 3 meetings of 0.49 in the medium category and learning outcomes with an average n-gain value of 0.69 in the moderate category. Therefore, the interactive e-module based on blended learning developed is feasible and effective to be used to improve students' independence and learning outcomes on acid-base materials.